2005
DOI: 10.1021/la047427u
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organization of Polystyrenes into Ordered Microstructured Films and Their Replication by Soft Lithography

Abstract: We report on the formation of ordered arrays of micrometric holes on the surface of polystyrene (PS) films cast from volatile solvents in the presence of humidity at different temperatures. The formation mechanism is investigated for PS having different molecular weights, polydispersities, and carboxylic terminations. Among the chosen materials, a highly regular honeycomb microstructured morphology is obtained on the surface of films prepared with dicarboxy-terminated PS with = 100,000. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
171
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 164 publications
(178 citation statements)
references
References 23 publications
(59 reference statements)
4
171
0
3
Order By: Relevance
“…Consider first the impact of the polymer structure on the resulting patter. Bolognesi et al reported that polar groups of polymer play a fundamental role in the process [37]. These results were supported by findings reported in Ref.…”
Section: Impact Of the Polymer Aarchitecture And Physical Parameters supporting
confidence: 80%
“…Consider first the impact of the polymer structure on the resulting patter. Bolognesi et al reported that polar groups of polymer play a fundamental role in the process [37]. These results were supported by findings reported in Ref.…”
Section: Impact Of the Polymer Aarchitecture And Physical Parameters supporting
confidence: 80%
“…The authors reported the advantages of 3-dimensional patterned surfaces as photonic crystal materials. 183 Stenzel and coworkers used a thermoresponsive block copolymer, PS-block-poly(N-isopropyl acrylamide), which was cast on a cold glass surface at 50% RH and -10…”
mentioning
confidence: 99%
“…Detailed mechanism of the honeycomb structure formation form PS layers during a different sample preparation mechanism is discussed by Bolognesi et al 29 Based on the similarity with the structures formed during chloroform dipping in our work, the hole formation mechanism may apply to our system. The authors have reported the formation of highly ordered two and three-dimensional patterns in linear PS with and without terminal polar groups.…”
Section: Figure 2 -Sem Images Of Multilayered Honeycomb (A) and Singmentioning
confidence: 56%